LeptoSafe: integrating digital health tools in early detection and prevention of leptospirosis - Rosli, Muhammad Amirul Afiq; Sahak, Irfan; Salleh, Norsaremah; Zein, Samer; Khairudin, Roslaili; Mohd Khairi, Amir Faisal; Kaderi, Mohd Arifin; Zainuddin, Norafiza (IIUM Press, 2025)
Background: Leptospirosis is a significant zoonotic disease endemic to tropical, flood-prone regions such as Pahang, Malaysia, where limited public awareness, delayed risk recognition, and overlapping symptoms with other febrile illnesses contribute to substantial underreporting and disease burden. Challenges in early detection and prevention necessitate innovative digital solutions to improve public health outcomes. Methods: LeptoSafe, a mobile health application prototype, was developed through a user-centred, iterative design approach involving collaboration with allied health experts and the Malaysian Ministry of Health. The app integrates evidence-based literature and real-time leptospirosis case data. Key components include a validated ten-item self-screening questionnaire for personalized risk assessment, GIS-enabled dynamic hotspot mapping with push notifications, educational infographics and videos, and a locator for nearby health facilities using Google Maps API. The platform supports bilingual access (English and Malay). Results: LeptoSafe integrates four core functionalities: (1) interactive self-assessment delivering individualized leptospirosis risk stratification; (2) real-time geospatial visualization of confirmed case clusters enhancing situational awareness; (3) comprehensive multimedia educational content tailored to local epidemiology; and (4) a health facility locator improving care accessibility. The prototype effectively addresses critical gaps in early symptom recognition, health knowledge dissemination, and timely healthcare engagement, particularly among vulnerable populations exposed to environmental and occupational risks. It represents a novel interdisciplinary advancement by integrating mobile technology, geographic information systems, and allied health expertise into a unified digital platform for zoonotic disease management. Moreover, LeptoSafe is among the first applications to combine real-time epidemiological data, risk self-assessment, and targeted education for leptospirosis prevention. Its modular and scalable design offers a replicable model for digital health interventions across neglected tropical diseases globally, enhancing surveillance capacity and public empowerment. Conclusion: LeptoSafe demonstrates the feasibility and impact potential of an integrated digital health platform to enhance leptospirosis control through empowerment, early detection, and prevention. Future directions include field deployment, rigorous evaluation of behavioural and knowledge outcomes, and integration with national surveillance systems to strengthen public health responses.